Investigation of the Mechanism of Action of New Hepatoprotective Herbal Drugs in the Experiment - Larysa V. Iakovlieva (Journal of Global Pharma Technology, 2018)
Introduction. Rational pharmacotherapy for liver disease remains one of the most urgent medical and social problems. The purpose of the study was to determine the mechanism of action of new hepatoprotectors of plant origin in the model of acute toxic lesions of the liver of rats (tetrachloromethane, 0.8 ml / 100 g body weight, once, intragastric). Materials & Methods. Animals were divided into 8 groups of 7 animals in each group: 1 group - intact control; group 2 - control pathology (CC14); 3-6 groups - animals that received capsules Hepafisan (108 mg / kg), Fitovenol (150 mg / kg) against the background of СС14; Granules Gepatrombin (900 mg / kg) and Polygerbagastrin (900 mg / kg), respectively; 7-8 groups - animals that were given drug comparisons capsules Silibor (100 mg / kg) and Gepabene  (88 mg / kg). The investigated preparations were administered to animals in the treatment-and-prophylactic mode: 1 hour before administration and 1 hour after tetrachloromethane administration and on the next day. On the 3rd day after the simulation of the pathology in the blood serum of animals were determined the activity of alanine, aspartate aminotransferase (AlAT and AsAT) of alkaline phosphatase (ALP), the content of circulating immune complexes, C-reactive protein (CRP), proinflammatory (interleukin 1, (IL1) and tumor necrosis factor (TFN-α) and anti-inflammatory cytokines (interleukin 10 (IL10), the content of total and direct bilirubin in the blood serum. The absolute mass of the liver was determined. The content of the secondary products of LPO-TBC-reactants was determined in blood serum and in the biological substrate (liver tissues) activity of superoxide dismutase (SOD) and catalase (CAT), pyruvic acid (Pyruvate), lactate in serum - activity of succinate dehydrogenase (SDG), the content of glycogen in the liver, the liver detoxification function was investigated using a functional test called "Thiopental sleep" (thiopental in dose 35 mg / kg, intraperitoneally). Research results. It has been established that Hepafisan, Fitovenol, Gepatropin and Polyherbagastrin stimulate of reparative and regenerative processes in a liver, eliminate inflammatory processes. Under the action of biologically active substances that are part of the plant, there is a normalization of the processes of phosphorylation, the restoration of the cytochrome P-450-dependent monooxygenase system. By enhancing the utilization of glucose, they contribute to the synthesis of glycogen and provide a high level of energy supply to cells, which is likely to stimulate synthetic processes and improve hepatobiliary system function.Conclusions. A crucial role in the mechanism of hepatoprotective action of investigated means plays antioxidant properties that reduce in the damaging effects of lipid peroxidation processes, which contributes to regeneration of hepatocytes and functional reactivation of the liver.Keywords: Model of acute toxic damage of the liver, Tetrachlorolmethane, New hepatoprotective plants preparations, Hepatoprotective action.